Comportamiento de la movilidad del municipio de Sopó proyectada al año 2034 como respuesta al crecimiento poblacional. (2022)
The purpose of the work is to analyze the behavior of mobility in the municipality of Sopó, composed of the road network and the facilities that complement the set of public space projected for the year 2034 based on the dynamics of population growth that the municipality of Sopó has presented. sopo in recent years, along with the increase in property units due to the development of housing projects also projected for the same year. The applied methodology focuses on a description and interpretation of the different scenarios of public space and comprehensive development based on both vehicular and pedestrian mobility presented today, projection to the year 2034 through Origin - Destination matrices and elements of social cartography, with which it seeks to explain the conditions of mobility together with the form of urbanization presented today, together with the direct incidence that this has with the roads, parks and other facilities that make up the municipality based on population growth.